Peroral cholecystoscopy using a multibending ultraslim endoscope through a lumen-apposing metal stent for endoscopic ultrasound-guided gallbladder drainage: a feasibility study - Yoo, Hae Won; Moon, Jong Ho; Lee, Yun Nah; Song, Yeon Han; Yang, Jae Kook; Lee, Tae Hoon; Cha, Sang-Woo; Cho, Young Deok; Park, Sang-Heum (Endoscopy, 2021)
Background Endoscopic ultrasound-guided gallbladder drainage (EUS-GBD) using a lumen-apposing metal stent (LAMS) has rendered endoscopic gallbladder assessment through a stent possible, but an appropriate endoscope is required. We assessed the feasibility of peroral cholecystoscopy (POCC) using a multibending ultraslim endoscope passed through a LAMS after EUS-GBD.Methods 14 patients with a LAMS for EUS-GBD who consecutively underwent POCC were included. POCC was performed using a multibending endoscope inserted through the LAMS. The primary outcome was the technical success rate, defined as complete endoscopic examination of the gallbladder from the orifice of the cystic duct to the fundus. The types of intervention and adverse events were recorded.Results 17 POCCs were performed in 14 patients. Of the 17 POCCs, 15 (88.2 %) were technically successful. Narrow-band imaging endoscopy was performed in 12 procedures (70.6 %), and cholecystoscopy-guided target biopsies were obtained in six. Gallstone extraction was performed in two patients. After POCC, all LAMSs remained stable and no adverse events were observed.Conclusions POCC using a multibending ultraslim endoscope can be effectively and safely performed through a LAMS after EUS-GBD.